The critical resistance of literature (theoretical issues and Latin America discussions) - Dalmaroni, Miguel Ángel (2018)
Literature and theory are writings of resistance with drastic critical effects: language blockages that put us before the absolutely other, obstructions of the impossible inscription of the real. Between the 1990s and the first decade of the 21st century, the post-theoretical field and the condemnation of thecultural devices of domination generated in Latin American academic criticism a sustained refutation of “literature” that denied anycritical value to any practice describable as literature.These efforts were certainly very productive in critical and political terms, no matter how much one agrees with their theses. However, both the growing multiplicity of social modes of reading and the philosophical impulse of recent theory seem not to have been greatly affected by the academic policies of “the resistance to literature”.